2020
DOI: 10.3390/f11111233
|View full text |Cite
|
Sign up to set email alerts
|

Study on Gene Differential Expression in Tetraploid Populus Leaves

Abstract: Polyploids exhibit different phenotypes compared to those of diploids in plants, and the important role of polyploids in tree breeding has been widely recognized. The transcriptomes detected by RNA-seq in the Populus triploid by doubling the chromosomes of the female gamete, in the triploid by doubling the chromosomes of somatic cells and the diploid with the parent were compared to reveal the patterns of gene expression of tetraploid leaves and their influence on growth. The results showed that the high expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
2
1
0
Order By: Relevance
“…Polyploid plants had higher levels of growth-stimulating phytohormones. In accordance with the results of this research, Zhang et al (2020) ascribed the growth advantages of polyploid Populus plants to enhanced biosynthesis rates of cytokinin, auxin, gibberellin, and photosynthetic capacity, which lead to greater carbon fixation and higher sugar/starch contents. Plant growth regulators and their related ratios varied dramatically during the blooming process in this study, revealing intricate hormonal connections.…”
Section: Discussionsupporting
confidence: 85%
“…Polyploid plants had higher levels of growth-stimulating phytohormones. In accordance with the results of this research, Zhang et al (2020) ascribed the growth advantages of polyploid Populus plants to enhanced biosynthesis rates of cytokinin, auxin, gibberellin, and photosynthetic capacity, which lead to greater carbon fixation and higher sugar/starch contents. Plant growth regulators and their related ratios varied dramatically during the blooming process in this study, revealing intricate hormonal connections.…”
Section: Discussionsupporting
confidence: 85%
“…Through gene ontology annotation analysis, it was found that differential genes were mainly enriched in metabolism and cell composition, and metabolism and cell composition mainly affected plant growth and metabolism, which was consistent with the results of morphological and physiological differences between diploid and tetraploid cowpea. It confirmed the results of previous studies on populus tetraploid that differential genes were mainly enriched in cell process and metabolic process (ZHANG et al, 2020). KEGG pathway analysis showed that the DEGs were significantly enriched in six pathways: flavonoid biosynthesis, degradation of other glycans, phenylpropane biosynthesis, starch sucrose metabolism, cutin, amber and wax biosynthesis, circadian rhythm plant pathway.…”
Section: Differential Gene Analysis Between Diploid and Tetraploidsupporting
confidence: 89%
“…Although Vm and Va phenotypes had similar expression values, it is worth noting the difference in ploidy between the two groups. Polyploid species tend to have higher expression of genes during genome analysis [ 66 , 67 ]. Hence, coupled with its unique morphological features and late flower bud development, theoretically doubling the expression levels in the Vm phenotypes could show strong up-regulation of the various genes to possibly explain why Vm is less susceptible to pathogens.…”
Section: Discussionmentioning
confidence: 99%